Routing and switching essentials companion guide - Cisco Networking Academy (Indianapolis : Cisco Press, 2014)
Routing and Switching Essentials Companion Guide is the official supplemental textbook for the Routing and Switching Essentials course in the Cisco® Networking Academy® CCNA® Routing and Switching curriculum.